2021
DOI: 10.1007/s00264-021-05097-z
|View full text |Cite
|
Sign up to set email alerts
|

Single-bone versus both-bone plating of unstable paediatric both-bone forearm fractures. A randomized controlled clinical trial

Abstract: Purpose This clinical trial compares the functional and radiological outcomes of single-bone fixation to both-bone fixation of unstable paediatric both-bone forearm fractures. Methods This individually randomized two-group parallel clinical trial was performed following the Consolidated Standards of Reporting Trials (CONSORT) statement at a single academic tertiary medical centre with an established paediatric orthopaedics unit. All children aged between n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
20
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(23 citation statements)
references
References 34 publications
(50 reference statements)
3
20
0
Order By: Relevance
“…The definition of unstable fractures in the distal forearm is unknown. Mohamed Khaled et al defined unstable diaphyseal fractures as diaphyseal fractures between the distal and proximal metaphysis, with an angle > 10°, and/or malrotation > 30°, and/or a displacement > 10 mm after an attempted closed reduction (15). Kay et al defined that the closed reduction of fractures of the middle ulna and radius over 10 years with an angle of more than 10°is unstable (16).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The definition of unstable fractures in the distal forearm is unknown. Mohamed Khaled et al defined unstable diaphyseal fractures as diaphyseal fractures between the distal and proximal metaphysis, with an angle > 10°, and/or malrotation > 30°, and/or a displacement > 10 mm after an attempted closed reduction (15). Kay et al defined that the closed reduction of fractures of the middle ulna and radius over 10 years with an angle of more than 10°is unstable (16).…”
Section: Discussionmentioning
confidence: 99%
“…A, white box illustrating metaphysis; from radial tuberosity to metaphysis, backbone regarded as backbone; backbone divided into three equal parts, followed by proximal, middle, and distal segments; B, in lateral radiograph, CD considered perpendicular to the epiphyseal plate of distal radius; angle between AB and CD considered the angle of radius fracture; angle between EF and GH considered the angle of ulna fracture; in the orthographic film, KL considered perpendicular to the epiphyseal plate of the distal radius, and angle between IJ and KL considered -3.7°(i.e., the angle of radius fracture). (15,(22)(23)(24), and consider that the failure rate of closed reduction in children over 10 years is high and the acceptable angle range is small. Finally, this study limited the age of children to 6 -9 years, thereby reducing the effect of age on fracture shaping.…”
Section: Discussionmentioning
confidence: 99%
“…Khaled et al enrolled 50 children between 9 and 15 years of age in a randomized controlled trial comparing the management of both-bone forearm fractures by plating only the ulna (single-bone technique) and the traditional method of plating both the ulna and the radius. They found that the single-bone technique yielded more reangulation but still achieved healing in an acceptable alignment with shorter operative times and equivalent functional outcomes 8 .…”
Section: Traumamentioning
confidence: 99%
“…P ediatric forearm fractures are common injuries, comprising nearly 40% of childhood fractures. [1][2][3][4][5][6][7][8][9][10][11][12] The most prevalent mechanisms of injury include fall on an outstretched hand and trauma. 4,13 After the fracture, these injuries have a wide range of treatments with indications depending on specific patient and fracture characteristics.…”
mentioning
confidence: 99%
“…12 Common treatment includes operative intervention, with plate or nail fixation, or nonoperative treatments such as casting. [2][3][4]7,9,[11][12][13] The general treatment consensus is to first attempt management with closed reduction and immobilization. 2 Surgery may be indicated in polytraumatic or open fracture settings, when the patient is nearing skeletal maturity, or when closed reduction is unsuccessful.…”
mentioning
confidence: 99%